A case of Fanconi syndrome accompanied by crystal depositions in tubular cells in a patient with multiple myeloma - Do Hee Kim; A Young Lim; Hye Bin Gwag; Ji Hyeon Lee; Ki Sun Jung; Keol Lee; Wooseong Huh; Dae Joong Kim; Yoon-Goo Kim; Ha Young Oh; Kihyun Kim; Gee-Young Kwon; et al. (The Korean Society of Nephrology, 2014)
Fanconi syndrome (FS) is a rare condition that is characterized by defects in the proximal tubular function. A 48-year-old woman was admitted for evaluation of proteinuria. The patient showed normal anion gap acidosis, normoglycemic glycosuria, hypophosphatemia, and hypouricemia. Thus, her condition was compatible with FS. The M peak was found behind the beta globulin region in urine protein electrophoresis. Upon bone marrow examination, we found that 24% of cells were CD138+ plasma cells with kappa restriction. From a kidney biopsy, we found crystalline inclusions within proximal tubular epithelial cells. Thereafter, she was diagnosed with FS accompanied by multiple myeloma. The patient received chemotherapy and autologous stem cell transplantation, and obtained very good partial hematologic response. However, proximal tubular dysfunction was persistent until 1 year after autologous stem cell transplantation. In short, we report a case of FS accompanied by multiple myeloma, demonstrating crystalline inclusion in proximal tubular cells on kidney biopsy.